Playing with Expectations: A Contextual View of Humor Development - Airenti, Gabriella (Frontiers in Psychology, 2016)
In the developmental literature it has been advanced that young children would not understand the specificity of nonliteral communicative acts. In this article I shall focus on young children’s ability to produce and understand different forms of humor. I shall explore children’s acquisition of the communicative contexts that constitute the background enabling them to perform humorous interactions before being able to analyze them in the terms allowed by a full fledged ToM. I consider that different forms of humor share a number of basic features and that we can draw a continuum from simple forms to sophisticated ones. In particular I shall focus on teasing, a form of humor already present in preverbal infants but also considered as a typical feature of irony. I shall argue that all forms of humor can be described in the terms of a kind of interaction that I propose to call “playing with expectations”.